Interfacial adhesion between silver ink and thermoplastic polyurethane and electromechanical reliability of flexible printed circuit - Mohd Yunos, Afiqah (2021)
Flexible printed circuit (FPC) is one of the promising components in the electronic industries. The advantages of FPC are that its fabrication process is environmentally friendly, low cost, and efficient, which makes it a favourable choice for applications in industrial and medical. The conductive ink and substrate are the main components of FPC and they need to perform with good flexibility as that indicates that it is able to withstand a degree of deformation before occurring loss in conductivity. Nonetheless, issues that arise are interfacial adhesion strength between conductive ink and substrate, and reliability of conductive ink upon exposure to a stretchable type of deformation. Therefore, this study aims to investigate two different adhesion-enhancing techniques, which are thermal control and self-assembled monolayer of adhesion promoter. In addition, reliability of the conductive ink when exposed to stretchable type of deformation is also investigated. The silver conductive ink and thermoplastic polyurethane (TPU) were used in this study. The thermal control technique involved curing printed silver conductive ink at selected temperatures: room temperature, 60oC, 80oC, 100oC, 120oC, 130oC, and 140oC. The TPU underwent thermal analysis by using Differential Scanning Calorimetry (DSC) to study thermal properties of TPU. Meanwhile, self-assembled monolayer technique involved the construction of adhesion promoter layer onto the surface of TPU by dipping it in the adhesion promoter solution. Adhesion promoter used in this study was 3-aminopropyltrimethoxy silane (APTS). The success of the APTS construction was evaluated through Fourier Transform Infrared Spectroscopy (FTIR) and water contact angle (WCA) analysis. The evaluation of adhesion performance was assessed according to the cross-cut test (ASTM D3359) and 180o peel-test. The changes in electrical, mechanical, and surface energy characteristics were carried out within this research to investigate whether these techniques would cause changes in the mentioned properties. The experimental results showed an improvement in adhesion when both methods were executed. The thermal control has 4B/0.22 N/mm to 5B/0.55 N/mm rating when curing started at 100oC to 140oC. APTS-treated TPU showed adhesion was improved to 3B/0.17 N/mm. An increase in conductivity of printed silver with lower hardness was observed when the temperature was elevated. However, insignificant changes in conductivity and hardness were observed for APTS-treated TPU. The surface energy of TPU changed when it was exposed to thermal, showing an insignificant effect in promoting the adhesion. The improvement of adhesion was described as influenced by the changes in thermal properties of TPU. Meanwhile, surface energy of APTS-treated TPU showed polar properties due to the presence of polar head functional groups that allowed affinity bond with the silver particles. Reliability of silver ink was tested by printing with different geometrical patterns (straight, square, sinusoidal, and zig-zag), and different widths (1 mm, 2 mm, and 3 mm). The electromechanical measurement was carried out by manually stretching the pattern until it lost its conductivity. Zig-zag with 3 mm width showed excellent electromechanical performance with 7.78% maximum strain.